Pentagalloylglucose reduces AGE-induced inflammation by activating Nrf2/HO-1 and inhibiting the JAK2/STAT3 pathway in mesangial cells - Jinzhi Tong; Jian Fang; Tiantian Zhu; Pan Xiang; Jiaojiao Shang; Lei Chen; Jindong Zhao; Yanxin Wang; Li Tong; Min Sun (Elsevier, 2021)
Pentagalloylglucose (PGG), a gallotannin polyphenolic compound, has been found to possess a host of beneficial pharmacologic activities, such as anti-inflammatory and antioxidative activities. We previously demonstrated that PGG is capable of binding to the cell membrane of renal mesangial cells, but the pharmacological effect of PGG on diabetic renal injury and the underlying mechanisms are still not yet clear. In this study, the effects of PGG on Nrf2/HO-1 and JAK2/STAT3 signaling were explored in AGE-stimulated mesangial cells. Furthermore, the Nrf2 transcriptional inhibitor ML385 was used to verify the involvement of Nrf2 in the PGG-mediated inhibition of the JAK2/STAT3 cascade. Our results showed that PGG signiﬁcantly inhibited AGE-induced ROS generation and activated AGE-inhibited Nrf2/HO-1 signaling. Moreover, AGE-induced inflammatory cytokines (IL-1β and TNF-α) and their signaling through JAK2/STAT3 were blocked by PGG. Furthermore, ML385 suppressed Nrf2/HO-1 signaling, elevated ROS and cytokine production, and activated JAK2/STAT3 cascade were reversed by PGG. These ﬁndings indicate that PGG inhibits the JAK2/STAT3 cascade by activating Nrf2/HO-1 signaling.